Safety and efficacy of lobaplatin combined with 5-fluorouracil as first-line induction chemotherapy followed by lobaplatin-radiotherapy in locally advanced nasopharyngeal carcinoma: preliminary results of a prospective phase II trial. Issue 1 (December 2017) - Ke, Liang-Ru; Xia, Wei-Xiong; Qiu, Wen-Ze; Huang, Xin-Jun; Yang, Jing; Yu, Ya-Hui; Liang, Hu; Liu, Guo-Ying; Ye, Yan-Fang; Xiang, Yan-Qun; Guo, Xiang; Lv, Xing
Abstract Background Due to improvements in imaging and radiological techniques as well as the use of chemotherapy, distant metastasis has become the predominant mode of treatment failure in patients with locally advanced nasopharyngeal carcinoma (LA-NPC). Platinum-based systemic chemotherapy has shown survival benefits and is now the standard strategy for systemic therapy in patients with LA-NPC. Notably, the third-generation platinum reagent lobaplatin has shown anti-tumor effects in several solid tumors with lower incidences of gastrointestinal, hepatic and renal toxicity relative to other platinum drugs. However, the safety and efficacy of lobaplatin as a first-line regimen in patients with LA-NPC are undetermined. Methods Patients with stage III–IVa-b NPC received lobaplatin at a dose of 30 mg/m2 on days 1 and 22 combined with a continuous 120-h intravenous injection of 5-fluorouracil at a dose of 4 g/m2 followed by lobaplatin at a dose of 50 mg/m2 on days 43 and 64 concomitant with intensity-modulated radiation therapy. Objective response rates and acute toxicity were assessed based on RECIST (1.1) and CTCAE v.3.0, respectively. Kaplan-Meier analysis was used to calculate survival rates. Results Fifty-nine patients were enrolled, and 44 patients (74.6%) received allocated cycles of chemotherapy. The objective response rates were 88.1% (95% confidence interval [CI], 0.77 to 0.95) and 100% after induction chemotherapy (ICT) and concurrent chemoradiotherapy (CRT), respectively. With a median follow-up period of 44 months, the 3-year estimated progression-free survival and overall survival were 86.4% (95% CI, 69.8 to 98.8) and 94.9% (95% CI, 89.5 to 100), respectively. The most common grade 3–4 toxicities were neutropenia (8.5%) and thrombocytopenia (40.7%) after ICT and CRT, respectively. Conclusion Lobaplatin combined with 5-fluorouracil followed by lobaplatin-RT treatment showed encouraging anti-tumor effects with tolerable toxicities in patients with LA-NPC. Randomized controlled trials of lobaplatin in patients with LA-NPC are warranted. Trial registration This trial was registered with the Chinese Clinical Trials Registry and approved on March 31st, 2012, numberChiCTR-ONC-12002060 .